2020
DOI: 10.3389/fncel.2020.581907
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis: Proteins, Proteostasis, Prions, and Promises

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by the progressive degeneration of the motor neurons that innervate muscle, resulting in gradual paralysis and culminating in the inability to breathe or swallow. This neuronal degeneration occurs in a spatiotemporal manner from a point of onset in the central nervous system (CNS), suggesting that there is a molecule that spreads from cell-to-cell. There is strong evidence that the onset and progression of ALS pathology is a consequence of protein misfolding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 453 publications
(664 reference statements)
1
22
0
Order By: Relevance
“…Changes in EV levels and cargo content are associated with health and disease, as well as responses to extracellular stimuli (Datta Chaudhuri et al, 2019;Margolis and Sadovsky, 2019). In the nervous system, EVs may promote neurodegeneration by transferring pathogenic molecules between neuronal and non-neuronal cells in a prion-like manner, which can "spread" disease (Soria et al, 2017;McAlary et al, 2020). Importantly, EVs also cross the blood-brain barrier (Saint-Pol et al, 2020), making them an attractive biomarker candidate for diseases of the central nervous system (CNS), including ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in EV levels and cargo content are associated with health and disease, as well as responses to extracellular stimuli (Datta Chaudhuri et al, 2019;Margolis and Sadovsky, 2019). In the nervous system, EVs may promote neurodegeneration by transferring pathogenic molecules between neuronal and non-neuronal cells in a prion-like manner, which can "spread" disease (Soria et al, 2017;McAlary et al, 2020). Importantly, EVs also cross the blood-brain barrier (Saint-Pol et al, 2020), making them an attractive biomarker candidate for diseases of the central nervous system (CNS), including ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Motor neuron degeneration in ALS results in progressive weakness and atrophy of multiple muscles, ultimately leading to loss of vital functions such as breathing. There is no effective treatment for ALS and most ALS patients die within 2 to 5 years following diagnosis (previously reviewed by Cook and Petrucelli, 2019;Mejzini et al, 2019;Kim et al, 2020;McAlary et al, 2020). The majority of ALS cases are sporadic, implying that the initial genetic causes and mechanisms triggering motor neuron loss are unknown.…”
Section: Involvement Of Astrocytes In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Since then, multiple deleterious variants in many genes have been described that either drive motor neuron degeneration, increase susceptibility to the disease, or influence the rate of disease progression in ALS. Pathogenic mutations of the genes TAR DNA BINDING PROTEIN (TARDBP), FUSED IN SARCOMA/TRANLOCATED IN LIPOSARCOMA (FUS), OPTINEURIN (OPTN), TANK-BINDING KINASE 1 (TBK1), as well as intronic expansions in the gene C9ORF72, are among the most frequent familial ALS mutations (previously reviewed by Cook and Petrucelli, 2019;Mejzini et al, 2019;Kim et al, 2020;McAlary et al, 2020;Ustyantseva et al, 2020). Motor neurons display alterations of numerous cellular mechanisms in ALS, including RNA metabolism, protein homeostasis and aggregation, nucleocytoplasmic trafficking, endoplasmic reticulum stress, dynamics of ribonucleoprotein bodies, mitochondrial biology, and autophagy, to name a few (Mejzini et al, 2019;Kim et al, 2020;McAlary et al, 2020).…”
Section: Involvement Of Astrocytes In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Whether the same will be observed in ALS remains unknown, in part because there are disagreements about the type of protein inclusions in ALS. Some studies found that ALS protein inclusions lacked key characteristics associated with amyloids and might instead by unstructured [13], whereas other reports identified prion‐like inclusions in ALS [53], similar to those observed in AD and PD [54].…”
Section: Introductionmentioning
confidence: 96%